1995
DOI: 10.1002/anie.199512301
|View full text |Cite
|
Sign up to set email alerts
|

Competing Pathways in the Reaction of Bis(pentafluorophenyl)borane with Bis(η5‐cyclopentadienyl)dimethylzirconium: Methane Elimination versus Methyl–Hydride Exchange and an Example of Pentacoordinate Carbon

Abstract: Filipin complex was obtained from Sigma (F-9765) as a crude mixture containing about 50% filipin 111 or from Upjohn (Lot 2923-DEV-39) containing about about 8 % filipin 111. It can be purified by reversed-phase preparative HPLC. The location of the C1' acetates in 3 and 4 were determined by their cross-peak in the COSY spectra with the readily identifiable C2 proton. The C15 acetate in 3 was identified by the simplicity of its coupling pattern. The location of the C7 acetate in 4 is less secure, and was assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A number of Zr borohydride complexes were prepared by Piers et al by the reaction of alkylzirconocenes with HB(C 6 F 5 ) 2 [29][30][31]. The complexes were found to be active in ethylene polymerization provided that additional alkylation with MAO takes place [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of Zr borohydride complexes were prepared by Piers et al by the reaction of alkylzirconocenes with HB(C 6 F 5 ) 2 [29][30][31]. The complexes were found to be active in ethylene polymerization provided that additional alkylation with MAO takes place [30].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, hydride complexes [Cp′4Zr2H3][B(C6F4R)4] (R = F, SiPr i 3), highly active initiators for the isobutene homopolymerization and isobutene-isoprene copolymerization, were described [28]. A number of Zr borohydride complexes were prepared by Piers et al by the reaction of alkylzirconocenes with HB(C6F5)2 [29][30][31]. The complexes were found to be active in ethylene polymerization provided that additional alkylation with МАО takes place [30].…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, a bis­(dihydroborate) adduct Cp 2 Zr­{(μ-H) 2 B­(C 6 F 5 ) 2 } 2 is prepared from Cp 2 ZrMe 2 and 4 equiv of HB­(C 6 F 5 ) 2 . Interestingly, the 11 B NMR shift in 7-tmeda is 15.6 ppm upfield from the signal for Cp 2 Zr­{(μ-H) 2 B­(C 6 F 5 ) 2 } 2 (−12.9 ppm, 1 J BH = 64 Hz) …”
Section: Resultsmentioning
confidence: 87%
“…In 1995, researchers have synthesized a zirconium complex (Cp 2 Zr[CH 2 (HB{C 6 F 5 } 2 ) 2 ]), which is the first mononuclear organometallic compound having a pentacoordinate carbon atom, in which the À CH 2 carbon is in the Hp conformation. [7] In 1996, Radius et al [1] have done a detailed theoretical study of a series of zirconium complexes and explored the effect of substituents, X (À H, À CH 3 ,À OH, À CN, À BH 3 À ) for axial hydrogens in the Hp methane. The results showed that the substitution of two axial hydrogen atoms by À BH 3 À reduces the energy barrier for the deformation from Td to the Hp structure.…”
Section: Introductionmentioning
confidence: 99%
“…In these complexes, a methylene carbon or alkyl group is bridging a binuclear metal centre (3c–2e bond) with lithium counter ions in the carbon ligand sphere. In 1995, researchers have synthesized a zirconium complex (Cp 2 Zr[CH 2 (HB{C 6 F 5 } 2 ) 2 ]), which is the first mononuclear organometallic compound having a pentacoordinate carbon atom, in which the −CH 2 carbon is in the Hp conformation . In 1996, Radius et al .…”
Section: Introductionmentioning
confidence: 99%